Non-IFRS and changes in accounting institutions : lessons from Nokia - Rautiainen, Antti; Järvenpää, Marko; Mättö, Toni (SAGE Publications, 2022)
We analyse the lessons learned from Nokia to illustrate the changing focus in accounting and organisational practices that affect the perceptions of relevant accounting work and the key measures of success. In the course of an analysis covering 25 years, the introduction of management accounting innovations was first emphasised regarding managerial relevance but were later replaced by financial accounting emphasis and innovations (e.g. non-IFRS reporting). Our data includes public reports, newspaper articles and 21 interviews made between 1996 and 2019. We present a framework for analysing shifts in the focus of accounting. Our case analysis on changing accounting practices, on shifting perceptions of relevance and reliability, and on primary measures of success, contributes to understanding the focus of key accounting measures in historical developments regarding perceived success or failure, and in changing institutional practices in terms of ‘institutional work’, especially through valourizing either the actions or valourizing reports.
Keywords: primary measures; institutions; work; accounting; change; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|